Typical and atypical metabolic characteristics of three iridaceae isoflavone components: in vitro and in silico studies - Gu, Jifeng; Zhang, Huishan; Wang, Mei; Zhou, Yuyang; Deng, Zhipeng; Shi, Rong (Frontiers in Pharmacology, 2025)
BackgroundBelamcanda chinensis (L.) DC (Chinese name Shegan) has been widely used because of its pharmacological activity and remarkable therapeutic effects in sore throat. Tectorigenin, irigenin, and irisflorentin have been recognized as important quality indicators in Shegan. However, the metabolic characteristics of isoflavone aglycones remain unclear.MethodsIn this study, human liver microsomes (HLMs) and Cytochrome P450 (CYP) recombinant enzymes were used to study the metabolic stability, identify the metabolic pathways and enzyme kinetics of these three components, and elucidate their possible binding sites through molecular docking.ResultsWhen tectorigenin, irigenin, and irisflorentin were co-incubated with HLMs and CYP recombinant enzymes, hydroxylation metabolite for tectorigenin, demethylated metabolite for irigenin, and 6,7-dihydroxy-5,3′,4′,5′-tetramethoxy isoflavone originating from irisflorentin were identified. CYP2E1 and CYP3A4 have high metabolic rates for tectorigenin, whereas CYP2C19 and CYP1A2 are the most important metabolic enzymes for irigenin and irisflorentin, respectively. The kinetics showed that the metabolism of tectorigenin and irigenin conformed to the Michaelis-Menten model, while the Eadie-Hofstee plot of irisflorentin yielded a convex curve with a unique “hooked” characteristic, and it conformed to the sigmoidal kinetics characteristic. Furthermore, molecular simulations showed that tectorigenin and irigenin bind to the orthosteric site of CYP isoforms via hydrogen bonds and π-π stacking, whereas irisflorentin is principally bound to CYP1A2 via π-π stacking and hydrophobic interactions.ConclusionCollectively, these Iridaceae isoflavone aglycones can be metabolized by CYP enzymes with typical or atypical kinetic characteristics. These results lay a foundation for a better understanding of the in vivo processes of these components.